2016
DOI: 10.1002/hlca.201500225
|View full text |Cite
|
Sign up to set email alerts
|

Two New Retigerane‐Type Sesterterpenoids from the Lichen Leprocaulon microscopicum

Abstract: In addition to classic chromatography methods, a liquid-liquid chromatography technique, namely centrifugal partition chromatography (CPC) was applied for the purification of compound 2. The structures were determined by analyses of mass spectrometry and 1D and 2D NMR data. Relative configuration of the isolated compounds was assigned on the basis of 2D NOESY experiments. The two compounds possess a rare pentacyclic carbon skeleton specific to lichen metabolism, quite unusual in the vegetal kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The unique structure of retigeranic acid has attracted widespread attention, , and a number of synthetic studies on retigeranic acid have been reported. In contrast, there have been few reports on its biosynthesis, though two plausible biosynthetic pathways have been proposed (Scheme ). ,, Shibata and co-workers proposed Route 1 . In this route, dissociation of the pyrophosphate of geranylfarnesyl diphosphate ( GFPP ) and sequential annulations (A-ring formation) yield a 5/15 bicyclic intermediate ( i ), which undergoes 1,5-hydrogen (H) shift to afford an allylic carbocation ( ii ).…”
mentioning
confidence: 99%
“…The unique structure of retigeranic acid has attracted widespread attention, , and a number of synthetic studies on retigeranic acid have been reported. In contrast, there have been few reports on its biosynthesis, though two plausible biosynthetic pathways have been proposed (Scheme ). ,, Shibata and co-workers proposed Route 1 . In this route, dissociation of the pyrophosphate of geranylfarnesyl diphosphate ( GFPP ) and sequential annulations (A-ring formation) yield a 5/15 bicyclic intermediate ( i ), which undergoes 1,5-hydrogen (H) shift to afford an allylic carbocation ( ii ).…”
mentioning
confidence: 99%